2022
DOI: 10.3354/meps14075
|View full text |Cite
|
Sign up to set email alerts
|

Body condition and migration timing of east Australian humpback whales

Abstract: In order to exploit seasonally favourable habitats for feeding and breeding, humpback whales Megaptera novaeangliae undertake one of the longest migrations in the animal kingdom. Stored energy is crucial for a successful migration, but few studies have investigated the relationship between migration timing and body condition in baleen whales. Using unmanned aerial vehicles, we quantified the body condition of east Australian humpback whales. We collected data on 513 individuals (48 calves, 166 juveniles, 251 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 75 publications
6
20
0
Order By: Relevance
“…However, the relationships identified in the current study were correlative in nature, and we are unable to identify exact mechanisms responsible for our findings, and we present hypotheses for further investigations. While the seasonal migration trends are well understood in this area (Chittleborough, 1965; Dawbin, 1966; Russell et al, 2022), the factors that determine the fine‐scale route of each whale are not known and the precise timings and routes of each migration ill‐defined. Options to gain this information in the future may be through additional satellite tracking technology or perhaps the creation of a high‐resolution sightings database which could include whale watching operators or citizen science.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationships identified in the current study were correlative in nature, and we are unable to identify exact mechanisms responsible for our findings, and we present hypotheses for further investigations. While the seasonal migration trends are well understood in this area (Chittleborough, 1965; Dawbin, 1966; Russell et al, 2022), the factors that determine the fine‐scale route of each whale are not known and the precise timings and routes of each migration ill‐defined. Options to gain this information in the future may be through additional satellite tracking technology or perhaps the creation of a high‐resolution sightings database which could include whale watching operators or citizen science.…”
Section: Discussionmentioning
confidence: 99%
“…The EAC is closest to the coast during winter when it is observed as near as 30 km from the coastline between 28° S and 32° S (Xie et al, 2021). During the annual migration, humpback whales are commonly observed moving north at the end of autumn (May–July) and south in spring (September–November) (Russell et al, 2022). Unfortunately, variations in the precise migration path (e.g., proximity to coast) taken by the humpback whales during their migration are not well understood, however it is clear that the whale's migration path overlaps with set fishing gear which is deployed along the continental shelf of New South Wales (NSW) and reports of entanglements with whales have increased over the last three decades.…”
Section: Introductionmentioning
confidence: 99%
“…Immature whales (calves and juveniles) experienced rapid increases in body condition over the course of the foraging season, reaching similar levels of BAI as mature whales by the beginning of April (Table 3, Figure 4). Immature whales likely invest the stored energy accumulated on the foraging grounds toward skeletal growth during the breeding season, whereas mature individuals invest in reproduction (Lockyer, 1981;Christiansen et al, 2013;Christiansen et al, 2016;Irvine et al, 2017b;Christiansen et al, 2020b;Russell et al, 2022). It is important to note that BAI is a relative measure of body condition (energy stores) and mature whales have larger absolute measures of body condition compared to immature whales, as their larger body sizes with smaller surface area to volume ratios enable greater capacity for absolute energy storage and a lower mass-specific metabolic rate.…”
Section: Variation In Body Condition Increase Amongst Reproductive Cl...mentioning
confidence: 99%
“…UAS have been used to measure body condition in blue (Balaenoptera musculus), gray (Eschrichtius robustus), and northern (Eubalaena glacialis) and southern right whales (Eubalaena australis) (Christiansen et al, 2016;Durban et al, 2016;Christiansen et al, 2018;Lemos et al, 2020;Christiansen et al, 2021;Stewart et al, 2022;Torres et al, 2022). For humpback whales, studies have described trends in body condition along the migration routes (Christiansen et al, 2020b;Russell et al, 2022), the North Atlantic feeding grounds (Aoki et al, 2021), and the Western Australian breeding grounds (Christiansen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding baleen whale physiology, bioenergetics, and body condition is essential to increasing our knowledge about their ecology and potential trade-offs they may be making (Stevenson & Woods, 2006). Despite this, few studies have explored the relationship between humpback whale migration and body condition (Christiansen et al, 2016(Christiansen et al, , 2020Dalle Luche et al, 2021;Russell et al, 2022). Historical whaling data from BSD have suggested that individuals with larger energy reserves tend to arrive in WA waters substantially later, perhaps reflecting individual residency times on high latitude feeding grounds or prioritizing longer periods of feeding at high latitudes over arriving early to low-latitude breeding grounds (Irvine et al, 2017).…”
Section: Introductionmentioning
confidence: 99%